State of Market Intelligence Activities in Ghanaian Construction Firms: A Preliminary Study. - Joseph Asante; Ernest Kissi; Alex Acheampong; Edward Badu (Construction Economics and Building)
In the highly competitive business environment intelligence-gathering is key to the success of every strategy. This study assesses the current state of Market Intelligence (MI) activities in the construction firms (CFs) in Ghana. The data was collected through structured interviews with a sample of 56 CFs, each represented by either CEOs or top managers. To provide a clear perspective on the state of MI activities in CFs, the findings were evaluated using "The World Class MI Roadmap" framework developed Global Intelligence Alliance (GIA). It revealed that the current approach to MI activities in Ghanaian CFs can be described as reactive or "firefighting" in nature. This implies a lack of proactive strategic planning and a potential loss of business opportunities. Based on the results, it is evident that further research is needed to explore the specific types of MI monitored by CFs, establish indicators for assessing the effectiveness of MI utilization, and identify enabling measures to enhance the MI culture within CFs. It is worth noting that this study was limited to CFs in a single administrative region in Ghana, and generalizing these findings could benefit from the inclusion of more CFs from other regions. Meanwhile, CFs should work on fostering a culture that places a high value on MI acquisition, dissemination, and utilization across all phases of the project marketing life cycle.